2012
DOI: 10.2741/4055
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells in atherosclerosis

Abstract: Endothelial progenitor cells (EPCs) are involved in the maintenance of endothelial homoeostasis and in the process of new vessel formation. Experimental and clinical studies have shown that atherosclerosis is associated with reduced numbers and dysfunction of EPCs; and that medications alone are able to partially reverse the impairment of EPCs in patients with atherosclerosis. Therefore, novel EPC-based therapies may provide enhancement in restoring EPCs’ population and improvement of vascular function. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
108
0
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 226 publications
(254 reference statements)
0
108
0
10
Order By: Relevance
“…Collectively, this suggests that SIRT6 is a negative regulator of vascular oxidative stress and inflammation. In addition, our observational results on the negative modulation of SIRT6 levels in EPCs from diabetic patients open a new scenario in the signaling pathways underlying the EPC functional impairment during atherosclerosis and diabetes (20,22). However, although our findings suggest that diabetes determines an increase of oxidative stress, NF-kB activation, and SIRT6 expression, the mechanism by which SIRT6 acts in the regulation of the type 2 diabetic plaque phenotype is unknown.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Collectively, this suggests that SIRT6 is a negative regulator of vascular oxidative stress and inflammation. In addition, our observational results on the negative modulation of SIRT6 levels in EPCs from diabetic patients open a new scenario in the signaling pathways underlying the EPC functional impairment during atherosclerosis and diabetes (20,22). However, although our findings suggest that diabetes determines an increase of oxidative stress, NF-kB activation, and SIRT6 expression, the mechanism by which SIRT6 acts in the regulation of the type 2 diabetic plaque phenotype is unknown.…”
Section: Discussionmentioning
confidence: 48%
“…It is already known from experimental and clinical studies (22) that atherosclerosis is associated with a reduced number and dysfunction of EPCs. Here, for a better understanding of the molecular mechanisms underlying EPC impairment in atherosclerosis, we looked at the possible involvement of SIRT6 by evaluating its expression levels in EPCs isolated from the peripheral blood of 10 nondiabetic patients and 10 diabetic patients (5 current incretin users and 5 never incretin users).…”
Section: Sirt6 Protein Levels In Epcs From Diabetic and Nondiabetic Pmentioning
confidence: 99%
“…These results support the hypothesis that ox-LDL is able to induce the apoptosis of HUVECs. This is significant since atherosclerosis has previously been associated with progressive endothelial cell loss (31). Therefore, the present study provides a potential mechanism by which ox-LDL exposure may enhance oxidative injury, in particular via induction of ROS production and activation of caspase-3.…”
Section: Discussionmentioning
confidence: 86%
“…Clinical studies documented a decreased number of circulating EPCs in coronary artery disease (CAD) patients, suggesting that levels of circulating EPCs might be associated with vascular endothelial function and cardiovascular risk factors [17][18][19][20][21] . Hill et al [10] measured colony-forming units of EPCs from patients with different degrees of cardiovascular risk but without history of cardiovascular disease.…”
Section: Epc Number and Function In Cardiovascular Diseasesmentioning
confidence: 99%
“…It was also found that EPCs from subjects at high risk for cardiovascular events had higher rates of in vitro senescence than cells from subjects at low risk. Subsequently, it was demonstrated that reduced level of circulating EPCs independently predicts atherosclerotic disease progression and development of cardiovascular events [17][18][19] . Sen et al [17] , suggested that EPC determines the quality of the coronary collateral circulation.…”
Section: Epc Number and Function In Cardiovascular Diseasesmentioning
confidence: 99%